Light Emitting Diode Based Evanescent Wave Fiber Optic Chemical Sensor for Detection of Thiocyanate - Kulkarni, V.K.; Bendigeri, H.H.; Kulkarni, R.M. (Asian Journal of Chemistry, 2017)
The work describes the development of a cost effective and highly sensitive evanescent wave fiber optic chemical sensor for the detection of toxic weak acid dissociable of cyanide i.e. thiocyanate (-SCN) using light emitting diode. High sensitivity is achieved by using unclad portion of multimode sensor grade plastic clad silica fiber as a sensing element. Two photo detectors have been employed to detect output of core and cladding modes. Comparison study gives a description for sensitiveness over the range from 0.02 to 0.1 ppm of thiocyanate concentration.